DDCC-based meminductor circuit with hard and smooth switching behaviors and its circuit implementation. (July 2022) - Orman, Kamil; Yesil, Abdullah; Babacan, Yunus
Abstract: After the realization of memristors, researchers have focused on other nonlinear memory elements such as memcapacitors and meminductors. Many circuits are designed to emulate these mem-elements since it is not possible to find these components on the market as discrete circuit elements. This study presents a Differential Difference Current Conveyor (DDCC)-based meminductor circuit emulator able to produce both hard switching and smooth switching behaviors without changing any circuit topology. The proposed meminductor circuit consists of only two DDCCs, a single analogue multiplier, a transistor, and three grounded passive circuit elements. No other circuit elements such as a memristor or memcapacitor were used to obtain meminductive behavior. The frequency dependence, pulse response, transition from smooth switching to hard switching, and Monte Carlo analyses of the proposed meminductor were investigated. A meminductor-based regular spike generator was designed as an application of the proposed meminductor, and a regular spike train was successfully produced.